Development and psychometrics of the English version of the Itch Cognitions Questionnaire - Heckman, CJ; Schut, C; Riley, M; Ehlers, A; Valdes-Rodriguez, R; Kupfer, J; Gieler, U; Stapleton, JL (Public Library of Science (PLoS), 2020)
Background: The aim of this study was to validate the English version of the Itch Cognition Questionnaire in a sample of patients with chronic itch due to psoriasis or atopic dermatitis. An English-language version of an instrument assessing itch-related cognitions is needed since cognitions can contribute to a worsening of itch, and chronic itch is prevalent in English-speaking counties and internationally.